P131 Patients with hand osteoarthritis have a long duration of symptoms and significant pain scores at the time of referral to rheumatology services. (20th April 2020) - Ghaffar, Muhammad Tauseef; O'Sullivan, Miriam; Silke, Carmel; Whelan, Bryan
Abstract: Background: Osteoarthritis is the most common arthritic condition worldwide affecting 9.6% of men and 18% of women aged >60 years with an Irish prevalence >50 years of age is 17.3% for women and 9.4% for men. It can occur in any joint but is most common in the hip, knee and spine. It is also prevalent in the hand and can lead to significant pain and disability. The aim of this study was to examine the pattern and severity of hand osteoarthritis in patients referred to a regional rheumatology service. Methods: Consecutive patients seen in general rheumatology clinics of all ages and gender who had confirmed diagnosis of hand osteoarthritis based on the ACR criteria were recruited (patients with RA, psoriatic arthritis, gout and haemochromatosis were excluded). All gave written informed consent to participate and had a single assessment performed including demographic details, symptom assessment using the AUSCAN Osteoarthritis Hand Index. In addition, measures of functional ability, grip strength and pincer strength were performed in the OT department. All patients also had an up to date hand X-ray performed. For the purposes of this paper we will report the initial assessments including the demographic details and pain scores. Results: 103 consecutive patients were included in this analysis. M:F ratio 1:5.25. Mean age was 66.13 years. Mean duration of symptoms 74.63 months (8-422). At assessment the mean pain scores (0-10 VAS) were 4.53 (at rest), 6.09 (when gripping), 6.06 (when lifting) and 6.42 (when turning objects). The mean tender joint count was 7.14 and the mean score for objective soft tissue swelling in the joints was 1.36. Subject Average VAS (0-10) Pain Score at presentation by Gender Conclusion: From these analyses, we can see that patients are referred very late with no one being seen within 6 months of symptoms onset. This is despite patients having pain scores which are comparable to those with inflammatory arthritis and in a small minority evidence of soft tissue swelling in joints at the time of presentation. In addition, it is noticeable that men are under-represented in the cohort of referred patients based on estimates of prevalence. Disclosures: M. Ghaffar None. M. O'Sullivan None. C. Silke None. B. Whelan None.